Influence of Soil Amendments on the Rhizosphere Mycoflora of Dalbergia sissoo - , Yasmeen; Ajaz, Shamim (Indian Forester, 2003)
Qualitative and quantitative changes in rhizosphere mycoflora of D. sissoo due to soil amendements was studied. In all 28 species of fungi were isolated from the soil. Highest reduction in frequency and population of fungi was observed in soil amended with mustard cake followed by castor cake.